SERVICE QUALITY AND CUSTOMER SATISFACTION AT INDONESIAN FRANCHISE CUISINE - Hendra (Juremi: Jurnal Riset Ekonomi, 2022)
Whether in times of peace or turbulence, most SME focus on customer satisfaction have bring up interest, intention to purchase and loyalty. Since it is highly competitive industry, customer tend to choose better service quality that provided. The purpose is to empirically examine the relationship between service quality and customer satisfaction at one of the Indonesia Franchise Cuisine, in city of Medan, North Sumatera. Method used is a quantitative analysis to study the relationship between two variables, through distributing online questionnaires and interviews with adaptation of purposive or judgement sampling, which is investigated with linear regression, coefficient determination and hypothesis testing. It is concluded that service quality portrays strength of 79.2% in determining customer satisfaction and the remaining is influenced by other factors as example from price, product quality; finally results justify the existence of service quality influence towards customer satisfaction in Indonesian Franchise cuisine. It is recommended the franchise to improve the performance to achieve better result as this will increase the competitive advantage in the market, so that it is also ready for International Market, for example in Asia or other countries in the world. In addition, hiring more staff to improve the service delivery and provide training experience will increase performance.